Morphological ontogeny of Minunthozetes semirufus (Acari: Oribatida: Punctoribatidae) - Seniczak, Stanisław; Seniczak, Anna (Zootaxa, 2018)
The morphological ontogeny of Minunthozetes semirufus (C.L. Koch, 1841) is redescribed and illustrated. The juveniles of this species have a humeral organ and a gastronotal shield, which bears four pairs of setae (dm, dp, lp, h1) in the larva, and 10 pairs (d-, l-, h-series, p1) in the nymphs. In the larva, the anterior part of gastronotal shield (pygidium) reaches the insertions of setal pair dm. In the juveniles, the prodorsal and gastronotal setae are short, and in the nymphs setae of c-series are inserted on separate microsclerites. In the larva, 12 pairs of gastronotal setae are present, including h3, in the nymphs there are 15 pairs. In the nymphs of M. semirufus, solenidion ω2 on tarsus I is located anterolateral to solenidion ω1, whereas in the adult it is located posterior to ω1. In the tritonymph, seta l’ is added on femora I and II, whereas seta l” on these femora is added in the adult, which is unique in Punctoribatidae.